2008
DOI: 10.1029/2007jc004370
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability and Po River plume influence on biochemical properties along western Adriatic coast

Abstract: [1] The influence of the Po plume on the northern Adriatic Sea was observed during two seasons in 2003 under distinct physical forcing regimes. During the winter, the plume was cool, low in both salinity and chlorophyll, but with higher chlorophyll concentrations occurring along the plume boundary. The plume mixed deeply in the water column in response to the strong wind forcing. The northern Adriatic and the Po plume cooled significantly during the observational period, and therefore salinity alone was the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 19 publications
(30 reference statements)
3
51
0
Order By: Relevance
“…Numberger et al (2009) showed that along the African coast where the surface waters are oligotrophic during summer the species G. ruber type platys show a trend to deeper habitats (50 m). Along the southern Italian coast the nutrient content decreases offshore (Marini et al, 2008;Morović et al, 2006), which causes the species further away from the coast to live deeper in the water column. Fig.…”
Section: Temperature and Salinitymentioning
confidence: 99%
See 4 more Smart Citations
“…Numberger et al (2009) showed that along the African coast where the surface waters are oligotrophic during summer the species G. ruber type platys show a trend to deeper habitats (50 m). Along the southern Italian coast the nutrient content decreases offshore (Marini et al, 2008;Morović et al, 2006), which causes the species further away from the coast to live deeper in the water column. Fig.…”
Section: Temperature and Salinitymentioning
confidence: 99%
“…The Adriatic Sea behaves like a dilution basin in all seasons (Artegiani et al, 1997b). Besides the less saline water masses the river discharge brings large fluxes of nutrients into the basin (Marini et al, 2008).…”
Section: Hydrography Of the Adriatic Seamentioning
confidence: 99%
See 3 more Smart Citations